Pragmatic Study on Sallal’s Linguistic Behaviour in Addressing the Algerian Nation - Rebhi Belkacem, Ben Rabah (My University, 2017)
The current research aims to investigate The Algerian first minister Mr. Abdelmalek Sallal’s linguistic scandals when addressing the Algerian nation. This will lead us to ask the question whether these scandals are intentional or they are just a mirror of his political incompetence. Also, to explore how the public opinion interpret this phenomenon. As a response to the raised question, a sequence of suggested answers is presented. First, maybe these linguistic behaviour is deliberate according to the Algerians’ awareness. Second, the Algerians mostly find no relevancy to the linguistic choices that are uttered by the Prime Minister because they do not match his intentions. Third, Sallal’s linguistic performance is considered to be not appealing to his political status. Over and above, this language affects negatively on the national public opinion in terms of narrowing the circle of trust between the ruler and the ruled. The methodological process conducted is a qualitative approach where a linguistic analysis is used based on Austin’s speech act theory on a set of clips of some of Mr. Abdelmalek Sallal’s speeches. Through the implementation of this type of analysis on the collected data, it is understood that language plays a crucial role in politics and presentation of power; that is why its effect can be considered either positive or negative, depending on its users’ linguistic behaviour. As a consequence, from what is observed, language has a great impact on the Algerian citizens’ trust and impression towards their leaders and their hope for a prosperous future as well.
Keywords: Pragmatics, speech act; locutionary; illocutionary; Perlocutionary; Political discourse; Algerian Prime Minister